Sensing us in the world: new materialism as political theory - Brandt, Ingrid Helene (Politica, 2026)
This article explores new materialism as an approach within political theory and contributes to the understanding of how it challenges the anthropocentric foundations of modern political thought. In an era marked by climate change and ecological crises, new materialism invites us to rethink the relationship between culture and nature as deeply entangled and interconnected. The article argues that political theory must take seriously the fact that political landscapes are shaped by both humans and more-than-human assemblages. Drawing on the floods in Sydney during the 2022 La Niña weather phenomenon, the article demonstrates how New Materialism offers new concepts and sensibilities for political analysis. It shows how questions of agency, power, and critique can be understood differently when materiality is brought to life – not merely as a backdrop, but as an active participant in political processes. In this way, new materialism offers a radical rethinking of what political theory is, what it asks, and the ontological and epistemological premises on which it rests.